EFFECT OF A HEALTH LITERACY PROGRAM USING THE “HINSAMWAN MODEL” ON HEALTH PROMOTING BEHAVIORS AMONG BUDDHIST MONKS - เจริญชัย วัฏจักร; หีบแก้ว ปัดชาสุวรรณ์ นาฏนภา; บัญชรหัตถกิจ พรรณี (Primary Health Care Journal (Northeastern Edition), 2025)
Buddhist monks, as spiritual leaders, play significant roles in religion, society, and public health. Currently, monks are facing health challenges, particularly non-communicable diseases stemming from undesirable health behaviors. This quasi-experimental study aimed to evaluate the effects of a health literacy program designed to promote desirable health behaviors among Buddhist monks. The sample comprised 70 monks, divided into an experimental group (n=35) and a comparison group (n=35). The experimental group participated in the 12-week “HINSAMWAN Model” health literacy program. Data were collected using questionnaires and health assessments before and after the intervention, and analyzed using Paired t-test and Analysis of Covariance (ANCOVA) with a significance level of 0.05. The results showed that after the intervention, the experimental group had significantly higher mean health literacy scores than the comparison group across all six dimensions: accessing information (X̅diff = 9.99), understanding (X̅diff = 4.61), interaction (X̅diff = 6.43), decision-making (X̅diff = 8.69), behavioral change (X̅diff = 8.46), and advocacy (X̅diff = 12.67). Furthermore, the monks’ desirable health behaviors improved significantly (X̅diff = 3.00, 95% CI: 2.38 to 3.62). Health outcomes also showed significant improvements, with reductions in Body Mass Index (X̅diff = 1.11), waist circumference (X̅diff = 2.11), blood glucose levels (X̅diff = 9.03), and cardiovascular disease risk (X̅diff = 1.24). Therefore, compared to the comparison group, the program was effective in promoting health literacy and desirable health behaviors among Buddhist monks.